2022
DOI: 10.1167/tvst.11.4.23
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Investigation of Contrast Sensitivity and Disk Halo in High Myopia Treated With SMILE and EVO Implantable Collamer Lens Implantation

Abstract: Purpose To investigate the clinical outcomes in small incision lenticule extraction (SMILE) and EVO implantable Collamer lens (ICL)–treated high myopia. Methods Thirty-three SMILE-treated and 32 EVO ICL-treated patients were included and followed up for 6 months. Subjective refraction, contrast sensitivity, and disk halo size were measured preoperatively and postoperatively. Patient-reported outcomes (PROs) were obtained at the final visit. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…58% of the patients reported a worsening in night vision symptoms (mostly nonspecific glare and halo or starburst) after surgery, but overall levels of satisfaction were high [ 46 , 47 ]. The incidence of halo after ICL implantation was 68.8%, and that of starburst was 43.8% [ 48 ]. Glare/halo was present in 39% of eyes at 1 month, 32% at 3 months, 24% at 6 months, and improved to 15% of eyes at 12 months.…”
Section: Summary and Treatment Of Postoperative Complications Of Iclmentioning
confidence: 99%
“…58% of the patients reported a worsening in night vision symptoms (mostly nonspecific glare and halo or starburst) after surgery, but overall levels of satisfaction were high [ 46 , 47 ]. The incidence of halo after ICL implantation was 68.8%, and that of starburst was 43.8% [ 48 ]. Glare/halo was present in 39% of eyes at 1 month, 32% at 3 months, 24% at 6 months, and improved to 15% of eyes at 12 months.…”
Section: Summary and Treatment Of Postoperative Complications Of Iclmentioning
confidence: 99%
“…13,17,55 However, three studies reported a higher percentage of eyes gaining one or more lines of CDVA in the ICL group. [16][17][18] The preservation of CDVA is measured as a safety index; importantly, it is similar to or higher after ICL implantation than that after laser refractive surgeries [16][17][18][19]47,48,56 In our review of literature on the safety index of hole-ICL implantation published between October 2018 and October 2022, the weighted average safety index was 1.19 (Table 1), which was slightly higher than the safety index of 1.15 in a previous review by Packer in 2018. 46…”
Section: Cdva and Safety Indexmentioning
confidence: 57%
“…Halo was the most commonly reported night vision disturbance in the ICL group (91%), although it was considered to be non-distressing in more than 90% of cases in both groups. Halos after conventional ICL implantation have been reported in previous studies [ 10 , 11 , 33 ] and were found to be associated with differences between the mesopic pupil size and ICL optic zone diameter, and white-to-white diameter of the cornea [ 11 ]. Regarding EVO-ICL, apart from the edge of the optical zone, the cylindrical inner wall of the central hole can be an additional optical surface causing light phenomena [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 90%